A Content Analysis of Online Suicide Notes: Attempted Suicide Versus Attempt Resulting in Suicide. Issue 6 (28th September 2017) - Synnott, John; Ioannou, Maria; Coyne, Angela; Hemingway, Siobhan
Abstract : Fifty suicide notes of those who died by suicide and 50 suicide notes of those who survived their suicide attempt were analyzed using Smallest Space Analysis. The core of all suicide notes was discovered to be constructed with the use of four variables: saying goodbye to their audience, feelings of loneliness, method used to attempt suicide, and negative self‐image . Furthermore, three different suicide note themes of those who died and three suicide note themes from those who survived were also identified. The analysis revealed that suicide note writers who died by their attempt were more likely to combine a dislike of themselves and a concern for loved ones. The implications of the work in terms of suicide prevention are discussed.